Directors' Informational Role in Corporate Voluntary Disclosure: An Analysis of Directors from Related Industries - Ke, Ruihao; Li, Meng; Zhang, Yuan (Contemporary Accounting Research, 2020)
ABSTRACT Boards of directors play their role in corporate governance by advising and/or monitoring managers. In the corporate disclosure literature, prior research has documented directors' monitoring role, yet empirical evidence on directors' advising role is limited. Since the advising role often entails information transfer, we examine directors who concurrently serve as directors or executives in the firms' related industries (DRIs) and hence possess valuable information about the firms' external operating environment. We hypothesize and find that more DRIs on boards are associated with more accurate management forecasts. This association is stronger when firms face greater uncertainty, and holds in settings where DRIs are unlikely to monitor managers, suggesting a distinct advising role of DRIs. Our study highlights directors' role as information suppliers and advisors who help shape corporate voluntary disclosure.